1999
DOI: 10.1074/jbc.274.5.2916
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxide Rather Than Histidine Is Coordinated to the Heme in Five-coordinate Ferric Scapharca inaequivalvisHemoglobin

Abstract: The ferric form of the homodimeric Scapharca hemoglobin undergoes a pH-dependent spin transition of the heme iron. The transition can also be modulated by the presence of salt. From our earlier studies it was shown that three distinct species are populated in the pH range 6 -9. At acidic pH, a low-spin six-coordinate structure predominates. At neutral and at alkaline pHs, in addition to a small population of a hexacoordinate high-spin species, a pentacoordinate species is significantly populated. Isotope diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
1
6

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 48 publications
4
30
1
6
Order By: Relevance
“…Otzen and Oliveberg (Otzen et al, 2002), studying a small protein S6 in the presence of SDS, argue that monomeric SDS binds to the native state, but global unfolding would occur only above the critical micelle concentration (cmc). Indeed, this verification is corroborated for various works about interaction between surfactants and hemoproteins (Oellerich et al, 2003;Tofani et al, 2004;Das et al, 1999). Oellerich and coworkers (Oellerich et al, 2003), analyzing the interaction between SDS and cytochrome c, explain that the differences observed below and above the cmc are due to the different modes of binding of SDS monomers and micelles.…”
Section: The Interaction Between Hbgp and Surfactants As Resource Of supporting
confidence: 60%
See 1 more Smart Citation
“…Otzen and Oliveberg (Otzen et al, 2002), studying a small protein S6 in the presence of SDS, argue that monomeric SDS binds to the native state, but global unfolding would occur only above the critical micelle concentration (cmc). Indeed, this verification is corroborated for various works about interaction between surfactants and hemoproteins (Oellerich et al, 2003;Tofani et al, 2004;Das et al, 1999). Oellerich and coworkers (Oellerich et al, 2003), analyzing the interaction between SDS and cytochrome c, explain that the differences observed below and above the cmc are due to the different modes of binding of SDS monomers and micelles.…”
Section: The Interaction Between Hbgp and Surfactants As Resource Of supporting
confidence: 60%
“…In agreement with this discussion, Tofani and co-workers (Tofani et al, 2004) observed for Horse myoglobin (MbH), that only in a SDS/MbH ratio higher than 400, would occur a more significant protein unfolding and, for consequence, a more exposed and accessible heme pocket. Studies focused on the SDS-cytochrome c interaction at neutral pH have demonstrated that the unfolded state is stabilized when occur the bis-histidine (hemichrome) species formation, being that subsequent modifications of the secondary structure are rate-limited by the histidine dissociation rate (Das et al, 1999). Therefore, the hemichrome formation anchors the E helix into the ferric center, and, with the E and F helices maintained connected to the metallic center, the new polypeptide chains arrangement is stabilized, at least partially.…”
Section: The Interaction Between Hbgp and Surfactants As Resource Of mentioning
confidence: 99%
“…In conjunction with the visible titration, the acidic 6-c HS form is assigned to the Fe(III)-H 2 O adduct of heme-PhuS, whereas the two 6-c species observed at neutral pH are assigned to 6-c LS and 6-c HS heme hydroxide adducts. The 5-c HS heme form observed at pH 7.2 and above could have either a histidine or a hydroxide as the fifth heme ligand; there is precedent for both (33)(34)(35). The persistence of 6-c LS heme at acidic pH suggests that the acid-base transitions involving an exogenous axial ligand do not account for all of the heme.…”
Section: Resultsmentioning
confidence: 99%
“…Entretanto, a hemoglobina Scapharca inaequivalvis também mostra uma forte dependência do pH, quando da formação de uma espécie pentacoordenada, mesmo contendo a histidina na posição distal 33 . Esta informação é de grande relevância para o presente trabalho, uma vez que o trabalho de Madura e colaboradores 15 estabeleceu que as hemoglobinas de L. terrestris e Scapharca inaequivalvis apresentam significativa similaridade em termos de estrutura secundária.…”
Section: Figura 2 (A) Espectros Eletrônicos Do Monômero D Reconstituunclassified
“…De fato, sabendo-se que alguns trabalhos correlacionam a formação de hemicromo à ocorrência de determinados canais de acesso ao solvente 31 , este fenômeno poderia ser, a priori, simplesmente uma mudança conformacional, sem uma perda mais expressiva das estruturas secundária e terciária da proteína. Mesmo em trabalhos envolvendo as duas mais novas globinas descobertas em vertebrados, neuroglobina e citoglobina, a formação de hemicromos e seu estudo espectroscópico tem sido de grande importância, visando a compreensão das propriedades dessas hemoproteínas 32,33 . Neste sentido, vale lembrar que Blumberg e Peisach consideram a transição de spin que leva à formação do hemicromo como uma conseqüência da quebra de ligações hidrofóbicas 34 , o que implicaria, de qualquer maneira, em um maior ou menor rearranjo, enfatizando, uma vez mais, a correlação entre mudanças na primeira esfera de coordenação e alterações conformacionais das cadeias polipeptídicas.…”
Section: Introductionunclassified